A study on major cardiovascular risk factors in Acute Coronary Syndrome (ACS) patient 40 years and below admitted in CCU of Shahid Gangalal National Heart Center. - Adhikari, Chandra Mani; Rajbhandari, R; Limbu, YR; Malla, R; Sharma, R; Rauniyar, B; Rajbhandari, S; Baidya, S; Sharma, D; Maskey, A; et al. (Nepalese Heart Journal, 2013)
Coronary artery disease (CAD), predominately manifest in older individuals, is a devastating disease precisely because an otherwise healthy person in the prime of life may die or become disabled without warning. When the afflicted individual is under the age of 40, the tragic consequences for family, friends, and occupation are particularly catastrophic and unexpected. Fortunately, the incidence of myocardial infarction (MI) and symptomatic CAD in young adults is low; most studies show that only about 3% of all CAD cases occur in this age range. Premature CAD is defined as cardiac events occurring before the age of 45 in men and 55 in women. In its severe form it is defined as CAD occurring below the age of 40 years. Prematurity and severity suggests that the disease starts at an early age and has a malignant course. In this study, we aim to investigate the major risk factor (smoking, Hypertension, Diabetes and dyslipidemia ) as defined by ACC-AHA pattern in ACS patient 40years or below admitted in Shahid Gangalal National Heart Centre (SGNHC) from April 2008 to April 2009. There were all together 54 ACS patients, male 44(81%) and female 10(19%). HTN is the risk factor which was more commonly diagnosed and treated, while Dyslipidemia, DM and IFG were not usually diagnosed in young patient before they were diagnosed CAD. Dyslipidemia was the most common comprising 83.3% followed by HTN 70%, smoking 70%, abnormal blood glucose level 50%, DM in 22.2% while IFG in 27.7 %. High total cholesterol (48%) is the common form of dyslipidemia followed by high LDL (44.4%), low HDL in 31.4%. When non modifiable risk factor family history is excluded, 85% of the patients have two or more risk factors of CAD. When smoking along with family history is excluded 94.5% of the patients have 1 or more risks factors for CAD. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 20-24 DOI: http://dx.doi.org/10.3126/njh.v7i1.8497